Improving Students Skills in Writing Letters of Commerce by Developing Correspondence Module-based POE (Predict-Observe-Explain) - Novita Kumalasari; Madziatul Churiyah; Erna Sukmawati (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2017)
The purpose of this study is: generate a module-based POE (Predict-Observe-Explain) correspondence on the subject matter of making procedures commercial letters, know the feasibility of module, and knowing the difference skill writing letters that do not use the modul correspondence with the letter writing skills using a module correspondence. This type of research and development and modul after being validated matter expert, expert modules, and 12 students with result very valid/usable. The skills of letter writing in students with t-test calculations in SPSS, it is known that a significant difference between the average student learning outcomes experimental class and control class.